Implementation of Transformational Leadership in Sexual Harassment and Bullying Prevention Programs in Islamic Boarding Schools - Muhammad Erihadian; Dian Wildan; Harsing; Basuki; Isnan Rijibillah (PT Inovasi Pratama Internasional, 2024)
Islamic boarding schools, as the oldest Islamic educational institutions in Indonesia, have a strategic role in shaping the character and morals of the younger generation based on Islamic values. However, in recent years, cases of sexual harassment and bullying in Islamic boarding schools have become a serious concern. Data from the National Commission on Violence Against Women (2021) shows more than 500 cases of sexual harassment in educational institutions, including Islamic boarding schools. In addition, around 60% of students in Islamic boarding schools experience bullying in various forms (LPA, 2020). This phenomenon indicates the weakness of the leadership system in Islamic boarding schools in creating a safe environment. This study aims to analyze the application of transformational leadership in the program to prevent sexual harassment and bullying in Islamic boarding schools, with a focus on identifying supporting factors for success and developing an implementation model that can be adapted by other Islamic boarding schools. The method used is a qualitative approach with a case study at the Mardhatillah Islamic Boarding School, Rancaekek, Bandung Regency. The research findings show four main aspects in the implementation of transformational leadership: empowerment of students through the formation of a Task Force, an integrated communication and supervision system, active collaboration with parents and the community, and a commitment to sustainable development. This program successfully created a culture of mutual respect and a safe environment for students. This study provides theoretical contributions in the development of a transformational leadership model for preventing violence in Islamic boarding schools and offers a model that can be applied in other Islamic boarding schools to address similar issues.